Estudio de alcantarillado sanitario y pluvial lotización el Cielo de Jerusalén II parroquia urbana Emiliano Caicedo, Daule, Guayas - Cabrera Herrera, Wilson Ángel (2013)
The present research project aims, the study of sanitary and rain drainage system for Lotización the sky of Jerusalem II, located in the Urbana Emiliano Caicedo parish of the canton Daule, Guayas province based on actual and technical criteria adjusted to the socio-economic reality. Thus plan and create a development to improve the standard of living of its inhabitants in the area of health as the sector reference does not have any system of collection, disposal and treatment of sewage and rain. For this purpose is analyzing several alternative solutions, where considered for the optimization of the project are: the point of view technical, economic and environmental content, selecting the alternative that I offer the additional guarantees and advantages………